MODEL SIQRA (SCHOOL ISLAMIC QUR’AN REBRANDING APPROACH) DALAM REKONTRUKSI CITRA DAN IDENTITAS MADRASAH IBTIDAIYAH TARBIYATUS SIBYAN - Moh Syaikhol Hadi; Mohamad Joko Susilo (Jurnal Manajemen Pendidikan, 2025)
This study examines the reconstruction of institutional image and identity of an Islamic elementary school through the implementation of the SIQRA Model (School Islamic Qur’an Rebranding Approach) at MI Tarbiyatus Sibyan. The urgency of this research arises from declining public trust caused by institutional crises, weak institutional differentiation, and the lack of integration between branding strategies and Qur’anic values as the core identity of Islamic educational institutions. This study aims to analyze the implementation process of the SIQRA model and its implications for institutional image formation, identity reconstruction, and public trust in madrasah. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews, participatory observation, and document analysis involving the principal, teachers, school committee, students, and community members. Data analysis followed an interactive model consisting of data reduction, data display, and conclusion drawing, with data validity ensured through triangulation. The findings reveal that the SIQRA model is effective in reconstructing the institutional image and identity of the madrasah by strengthening Qur’anic values as the core identity, applying transformational leadership, developing flagship Qur’an memorization programs, and optimizing public communication and digital branding.